A photodetector for red and green with balanced negative and positive photocurrent for imaging is realized - Xuan Pu; Rongli Deng; Guanzhao Yang; Wenfeng Zhang; Haibin Lin; Junyong Li; Richard Nötzel (Scientific Reports)
Abstract A dual-polarity, photovoltaic photodetector for red-green dual-wavelength detection is demonstrated, operating in the self-powered mode. It is based on a core-shell n-InGaN nanowire/p-Cu2O heterostructure with inner upward energy band bending and near surface downward energy band bending. This produces negative photocurrent for red light illumination and positive photocurrent for green light illumination. Balanced negative and positive photocurrents are obtained by optimizing the Cu2O layer thickness. The imaging capability is experimentally demonstrated for real-life red and green color recognition on a mobile phone display.